Penilaian maturasi skeletal menggunakan radiograf Vertebra servikal dan pergelangan tangan - Michelle; Kusnoto, Joko (Jurnal Kedokteran Gigi Terpadu, 2024)
Introduction: Determining skeletal maturity is crucial in determining orthodontic treatment planning and treatment timing. The timing of orthodontic treatment is influenced by the patient's maturation stage, but each person develops at a different rate. Biological age, which considers body growth, is more accurate measure than chronological age. Radiograph of the cervical vertebrae and wrist bones can be used to assess maturity. Objective: This review aims to investigate the assessment of skeletal maturity using cervical vertebrae (CVMS) and hand-wrist (HWM) radiographs. Discussion: CVMS and HWM are two common methods for assessing skeletal maturity. CVMS utilizes lateral cephalometric radiographs, while HWM employs hand-wrist radiographs. Both methods offer advantages, such as simplicity and correlation with other maturity indicators. However, each method also has limitations, including subjectivity and radiation exposure. Conclusion: CVMS and HWM methods are valuable tools for assessing skeletal maturity in orthodontics. Dentists should carefully consider the advantages and disadvantages of each method when required to do growth assessment.